2005
DOI: 10.1207/s15328015tlm1701_5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Skills of 3rd-Year Students Who Completed Structured Clinical Skills Program With 6th-Year Students Who Acquired Clinical Skills in Unsystematic Way

Abstract: The clinical skills training given through a structured program that is widespread in the early years of medical school makes a great contribution to the development of students' clinical skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In general, student participation in structured skills training is associated with improved assessment outcomes - with respect to physical examination compared to students just following a clerkship [15] and with respect to injection and suturing skills compared to students not participating in a specific training program [26]. Different types of structured skills training programs have been developed leading to different outcomes with respect to students’ performance regarding physical examination skills or suturing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, student participation in structured skills training is associated with improved assessment outcomes - with respect to physical examination compared to students just following a clerkship [15] and with respect to injection and suturing skills compared to students not participating in a specific training program [26]. Different types of structured skills training programs have been developed leading to different outcomes with respect to students’ performance regarding physical examination skills or suturing.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the context of the study the influence of the same variable can lead to different results making it all the more difficult to give comprehensive recommendations which is the best method to teach which basic practical skill. One recommendation that can be given unrestrictedly is, that providing a skills training of any sort seems to lead to better skills learning in undergraduate medical education than just participating in usually unstructured clerkships or bedside teaching [15], [20], [50]. Whether the optimal instructor : student ratio (1:4) that was identified for learning suturing [7] will also be optimal for, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that this was not intended as substitute to in-person teaching but aimed to address the ‘see one’ aspect and ensure that students would not practice incorrect technique when the opportunity to practice became available. Where previous programmes have demonstrated that clinical skills taught with a regular structured programme showed better OSCE results49–51), ANTPS taught anaesthetic skills and knowledge in a structured format (figure 1). With increased confidence in anaesthetic core skills and thereby confidence in passing OSCEs (figure 5B), we recommend a novel literature-supported semilive approach of prerecorded OSCE-targeted skills videos within live structured teaching sessions 52.…”
Section: Discussionmentioning
confidence: 99%
“…None of these studies addressed which year in MS is optimal nor how many hours are needed with each method to prepare these students for proper PHPDS. [2][3][4][5][6][7][8][9][10][11] A study by Corbett et al 12 noted variability when physical examination skills were taught in the MS curriculum according to VOLUME however, it is at the discretion of the MS to determine when and how to teach the skills. 13 We have identifi ed 2 important outcomes of PHPDS in a medical curriculum.…”
Section: When and How Pediatric History And Physical Diagnosis Are Tamentioning
confidence: 99%